Pengaruh Pendapatan Asli Daerah, Dana Alokasi Khusus dan Dana Alokasi Umum Terhadap Pengalokasian Anggaran Belanja Modal Di Pulau Jawa - Nova Nabila; Okta Leviyani; Ahmad Syahril Azis; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of Regional Original Income (PAD), Special Allocation Funds (DAK), and General Allocation Funds (DAU) on the allocation of capital expenditure budgets on the island of Java. Capital expenditure is an important component in regional budgets that contributes directly to infrastructure development and improving public services. This study uses panel data from districts/cities on Java Island during the 2015-2020 period. The analytical method used is panel data regression with a fixed effects model (FEM) approach to identify the influence of independent variables on the dependent variable. The research results show that PAD has a positive and significant influence on capital expenditure. This indicates that regions with higher PAD tend to allocate more budget for capital expenditure. Meanwhile, DAK also has a positive and significant effect on capital expenditure, which shows that funds specifically allocated by the central government have succeeded in increasing investment in fixed assets in the regions. On the other hand, DAU was found to have a negative but insignificant effect on capital expenditure, indicating that general funds received from the central government did not directly encourage an increase in capital expenditure. This research provides important implications for regional policy makers in increasing PAD and utilizing transfer funds from the central government more effectively to accelerate the development of infrastructure and public services. Apart from that, the results of this research can also be a reference for further research in the field of regional finance and public budget management.